Evaluation of the Performance Improvement CME Paradigm for Pain Management in the Long‐Term Care Setting. Issue 3 (14th January 2014) - Fine, Perry G.; Bradshaw, David H.; Cohen, Mitchell J.; Connor, Stephen R.; Donaldson, Gary; Gharibo, Christopher; Gidal, Barry E.; Muir, James Cameron; Tselentis, Helen N.
Abstract Objective A performance improvement continuing medical education (PI CME) activity was designed to assist clinicians with accurately identifying and appropriately managing persistent pain in long‐term care facility (LTCF) residents. Design Volunteer LTCFs participated in a three‐stage PI CME model consisting of: 1) baseline assessment, 2) implementation of practice improvement interventions, and 3) reassessment. Expert faculty chose performance measures and interventions for the activity. A champion was designated ateach LTCF to collect resident charts and enter data into an online database. Setting Eight LTCFs located across the United States participated in the activity. Patients Fifty resident charts were randomly selected by each LTCF champion (25 for stage 1 and 25 for stage 3); a total of 350 charts were reviewed. Interventions In addition to a toolkit containing numerous performance improvement resources, an in‐service meeting led by an expert faculty member was conducted at each LTCF. Outcome Measures Stage 3 data were collected 6 weeks after implementation of interventions and compared with stage 1 baseline data to measure change in performance. Results Aggregate data collected from seven LTCFs completing the PI CME activity through stage 3 revealed improvements from baseline in four of five performance measures. Conclusions This CME activity allowed for collection of data demonstrating performance improvement in persistent pain management. The tools used as part of the intervention (available at http://www.achlpicme.org/LTC/toolkit) may help other clinicians enhance their management of LTCF residents with persistent pain.